Visualization Wrath Mahendradatta Through Type Work Dance Dramatic: Visualisasi Kemurkaan Mahendradata Melalui Tipe Karya Tari Dramatik - Wiharto, Mochamad Fauzi; ., djajuk sasanadjati (Solah, 2024)
The phenomenon highlighted in this dance work is that the Queen whose title is Sri Gunapriya Dharmapatni, or better known as Mahendradatta is the main character in this dance work, who is the daughter of King Sri Makutawangsawardhana from the Isyana Wangsa (Medang Kingdom) dynasty of East Java. Queen Mahendradatta had a partner named Queen Maruhani Sri Dharmadayana Warmadewa or more famously, Raja Udayana from Warmadewa-Bali. This became an attraction for choreographers to visualize it as a dance work. The focus in Gunapriya Dharmapatni's dance work is divided into two elements, namely the form element which contains the concept of dramatic dance and the content element, namely Dharmapatni's wrath. The choreographer visualizes ideas using movement styles and develops physical exercise techniques through dramatic types based on the construction method 1 by Jacquiline Smith. The mode of presentation in this dance work is symbolic and representative. The dramatic design uses a single cone based on La Meri's theory. Dance accompaniment was created using music editor software . The aim of writing this article is to describe the form of presentation of Satya Biyung's dance work including title, theme, synopsis, style, technique and supporting elements, dance accompaniment, stage techniques, make-up and clothing. as well as the process of creating dance works based on Jacquiline Smith's theory. In order to create two elements of content and form in dance works, the choreographer discovered the development of a new creative process to create dramatic forms inspired by the environment, as a learning source for young people to be creative and create art.